Preservation of terminal branches of the palmar cutaneous branch of the median nerve in open carpal tunnel release - Montanari, Sara; Corzani, Marco; Luchetti, Riccardo; Atzei, Andrea (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2022)
Purpose Post-operative pain in the palm and scar area is the most common complication after carpal tunnel release and injury to the terminal branches of the palmar cutaneous nerve is generally considered one of the causes for this complication. The Authors performed an intraoperative study preserving the terminal branches of the palmar cutaneous branch of the median nerve and verifying the frequency, location and direction of the branches that cross an interthenar incision.Method and Material Eighty-five consecutive patients (57 F – 28 M, mean age 66 y) underwent carpal tunnel release between February and June 2021. The cutaneous branches crossing the incision were identified and preserved by careful dissection. Subsequently they were counted and classified by their direction and distance from the proximal border of the transverse carpal ligament.Results Sensory branches were found in 40 % of cases (34/85) and their origin was observed at an average of 1.05 cm (0–1.8 cm) distal from the proximal border of the carpal tunnel. A total of 44 branches were observed of which 23 branches crossed the incision with a transverse course and 21 with an oblique, generally proximal-distal radio-ulnar course. The subcutaneous layer overlying the distal third of the transverse carpal ligament was found to be devoid of sensory branches, therefore it can be considered a relatively safe area.Conclusion Isolation and protection of palmar sensory branches is important for improving carpal tunnel release results. This goal can be more easily achieved by locating the skin incision on the distal third of the transverse carpal ligament, where the sensory branches have a lower frequency, possibly associated with a second proximal incision (biportal technique) to better visualize the proximal portion of the ligament and antebrachial fascia.
Keywords: Palmar cutaneous branch; Carpal tunnel release; Pillar pain; Median nerve; Ramus cutaneus palmaris